Knock‐in strategy at 3′‐end of Crx gene by CRISPR/Cas9 system shows the gene expression profiles during human photoreceptor differentiation. (26th January 2017) - Homma, Kohei; Usui, Sumiko; Kaneda, Makoto
Abstract : Fluorescent reporter gene knock‐in induced pluripotent stem cell (iPSC) lines have been used to evaluate the efficiency of differentiation into specific cell lineages. Here, we report a knock‐in strategy for the generation of human iPSC reporter lines in which a 2A peptide sequence and a red fluorescent protein (E2‐Crimson) gene were inserted at the termination codon of the cone–rod homeobox ( Crx ) gene, a photoreceptor‐specific transcriptional factor gene. The knock‐in iPSC lines were differentiated into fluorescence‐expressing cells in 3D retinal differentiation culture, and the fluorescent cells also expressed Crx specifically in the nucleus. We found that the fluorescence intensity was positively correlated with the expression levels of Crx mRNA and that fluorescent cells expressed rod photoreceptor‐specific genes in the later stage of differentiation. Finally, we treated the fluorescent cells with DAPT, a Notch inhibitor, and found that DAPT‐enhanced retinal differentiation was associated with up‐regulation of Crx, Otx2 and NeuroD1, and down‐regulation of Hes5 and Ngn2 . These suggest that this knock‐in strategy at the 3′‐end of the target gene, combined with the 2A peptide linked to fluorescent proteins, offers a useful tool for labeling specific cell lineages or monitoring expression of any marker genes without affecting the function of the target gene. Abstract : In this work, we have developed the human induced pluripotent stem cell (hiPSC) knock‐in lines those report specific gene expression without cloning of the promoter gene or affecting the gene function. Using CRISPR/Cas9 system, we successfully inserted the 2A peptide gene and fluorescent protein gene at 3′end of target gene, Crx. We believe this knock‐in reporter system is valuable not only for the labeling specific cell lineages but also for the monitoring expression of any marker genes whose promoters are not identified.